Insulin over expression induces heart abnormalities via reactive oxygen species regulation, might be step towards cardiac hypertrophy - Mushtaq, S; Ali, T; Gul, M; Javed, Q; Emanueli, C; Murtaza, I (Cellular and Molecular Biology, 2015)
Insulin is known to regulate blood-glucose level and promote its utilization as an energy source in cardiac tissues under normal physiological conditions as well as stimulates signaling pathways that involved cell growth and proliferation. Although recently insulin generated free radicals via NAD(P)H has been documented but the molecular mechanism is still under investigation. The aim of present study is to elucidate the reactive oxygen species (ROS) dependent possible role of insulin in cardiac abnormalities, including hypertrophy by regulation of antioxidants enzyme (SOD) activity. In the current study, 60 cardiac patients and 50 healthy individuals as well as the rat model with insulin administration were under investigation. Oxidant, anti-oxidant biochemical assays, hypertrophic marker expression via immunobloting and histopathology were performed. We observed statistically significant elevation of the reactive oxygen species level in the serum of patients as well as in the insulin administrated rat model, a mild expression of cardiac marker in experimental models along with abnormal histopathology of hearts. However, super oxide dismutase free radical scavenger activity was down regulated upon insulin treatment compared to control rats. Conclusively, the present study showed that over expression of insulin might stimulate cardiac hypertrophic signal via up regulation of free radicals and down regulation of antioxidants enzymes including SOD activity.